2000
DOI: 10.1098/rstb.2000.0699
|View full text |Cite
|
Sign up to set email alerts
|

Global spectral–kinetic analysis of room temperature chlorophyll a fluorescence from light-harvesting antenna mutants of barley

Abstract: This study presents a novel measurement, and simulation, of the time-resolved room temperature chlorophyll a £uorescence emission spectra from leaves of the barley wild-type and chlorophyll-b-de¢cient chlorina (clo) f 2 and f104 mutants. The primary data were collected with a streak-camera-based picosecond-pulsed £uorometer that simultaneously records the spectral distribution and time dependence of the £uorescence decay. A new global spectral-kinetic analysis programme method, termed the double convolution in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
52
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 49 publications
10
52
2
Order By: Relevance
“…The data also suggest that qE is unlikely to arise solely in the minor monomeric antenna proteins of PSII, as proposed many times (Gilmore et al, 1998;Ahn et al, 2008). These conclusions are consistent with the finding that, while no individual Lhcb protein appears to be obligatory for qE, each one may play a role in shaping the PSII macrostructure for the optimal combination of light harvesting and photoprotection and with studies on the chlorophyll b-less mutants with severely reduced PSII antenna size that showed strong reductions in NPQ capacity (Härtel et al, 1996;Gilmore et al, 2000). The disruptive effect of the depletion of Lhcb proteins on the PSII macrostructure is well documented .…”
Section: Discussionsupporting
confidence: 78%
“…The data also suggest that qE is unlikely to arise solely in the minor monomeric antenna proteins of PSII, as proposed many times (Gilmore et al, 1998;Ahn et al, 2008). These conclusions are consistent with the finding that, while no individual Lhcb protein appears to be obligatory for qE, each one may play a role in shaping the PSII macrostructure for the optimal combination of light harvesting and photoprotection and with studies on the chlorophyll b-less mutants with severely reduced PSII antenna size that showed strong reductions in NPQ capacity (Härtel et al, 1996;Gilmore et al, 2000). The disruptive effect of the depletion of Lhcb proteins on the PSII macrostructure is well documented .…”
Section: Discussionsupporting
confidence: 78%
“…Today, global spectral and kinetic methods are used to separate the PS I and PS II emission bands in leaves (see Gilmore et al, 2000;Chapter 21, Gilmore). Lombard and Strasser (1984) established the following method to obtain information about the excitation rate of the two photosystems at room temperature.…”
Section: A Simultaneous Fluorescence Transientsmentioning
confidence: 99%
“…Such single-chromophore systems are generally easier to study than chlorophyll-containing photosynthetic complexes: in photosynthetic systems excitation-energy transfer between chromophores takes place, which in case of too high excitation energies can result in singlet-singlet annihilation, Chapter 12 Streak-Camera Fluorescence a process that can distort the fl uorescence kinetics (Sauer and Debreczeny, 1996). Gilmore et al (2000Gilmore et al ( , 2003a nicely demonstrated the application of the streak camera to obtain timeresolved fl uorescence spectra of leaves. Spectral and kinetic differences between Photosystems I and II could be discerned but relevant spectral evolution was only observed for times longer than 100 ps.…”
Section: Introductionmentioning
confidence: 97%